Perencanaan Pengolahan Air Limbah Restoran Dan Bar di Surabaya - Soobirumbassa, M. Yureico; Rachmanto, Tuhu Agung (Jurnal Teknik Informatika dan Elektro, 2023)
Altoro restaurant and bar activities will produce domestic and kitchen wastewater which is estimated to have pollutant levels of 680 mg/l BOD, 1000 mg/l COD, 100 mg/l TSS, 200 mg/l oil and grease and a pH of 6. This figure does not meet the water quality standards according to PERMEN LHK Number 68 of 2016, so water treatment needs to be carried out before being discharged into water bodies. Characteristics that do not meet water quality standards will become a reference for planning waste water treatment. The technologies planned for use in wastewater treatment are Grease Traps and aerobic-anaerobic Biofilters. The efficiency of the grease trap is known to reduce BOD, COD, oil and grease respectively 77%, 77% and 95%. Aerobic-anaerobic Biofilter efficiency is known to reduce BOD, COD, TSS, Oil and Fat respectively 99%, 93%, 99% and 85%. Eluent water from the aerobic-anaerobic Biofilter meets quality standards and will be stored in a storage tank before being channeled to the sewer.